Fenomena Hoaks Bidang Kesehatan Sebagai Kejahatan di Dunia Mayantara - Asri, Ardison; Hainun, Nienne Aridyanthi; Saputra, Samsudin Jagat (Indonesian Journal Publisher, 2025)
False, fake, or untrue, even misleading news content better known as hoaxes related to the health sector is still one of the hoaxes that should be watched out for. Although the percentage is still inferior to political hoaxes and infotainment, the impact it has caused is not a joke. The purpose of this study is to find out about the phenomenon and impact of hoaxes in the health sector as a crime in cyberspace. To answer the problems in this study, the research method used is normative with statute approach and conceptual approach. The data analysis used is qualitative, while the data analysis method used is descriptive-analytical. From the research results, it was found that the phenomenon and impact of news and hoax content in the health sector did not only hit Indonesia but also hit several countries in the world. From the phenomenon and impact of hoaxes in the health sector in several countries, it turns out that it is not a joke. This phenomenon of hoaxes in the health sector is an anti-science movement. This means that hoaxes in the health sector are no longer about people's ignorance about which information is wrong and correct, but about how to deal with people's social attitudes and behaviors that are anti-science. If this is left unchecked and no change is made, health misinformation will continue to spread and this will certainly erode trust in the government, doctors, patients, institutions, and society.